Physical properties of bitumen containing diatomite and waste engine oil - Abdul Hassan, Norhidayah; Ruzi, Nur Azni; Mohd Shukry, Nurul Athma; Putra Jaya, Ramadhansyah; Hainin, Mohd Rosli; Mohd Kamaruddin, Nurul Hidayah; Abdullah, Mohd Ezree (Penerbit UTM Press, 2019)
The addition of modifier, either to replace bitumen or as an additive, could potentially improve the performance of conventional bitumen used in road construction. This study characterizes the physical properties of bitumen 80/100 penetration grade modified with diatomite powder and waste engine oil (WEO). Different percentages of WEO i.e. 1%, 2%, and 3%, were added with 1% diatomite to the bitumen. The conventional and modified bitumen samples were tested for penetration, softening point, viscosity, and loss on heating. Results showed that the increase of WEO content, particularly at 3% in the modified bitumen, has softened the bitumen with lower softening point and higher loss on heating than the unmodified sample. In contrast, the diatomite powder has shown potential in reinforcing the bitumen structure at high temperature based on higher viscosity obtained at 165°C compared to conventional bitumen.